Effect of Tumor Size on Long-Term Survival After Resection for Solitary Intrahepatic Cholangiocarcinoma - Kong, Junjie; Cao, Yukun; Chai, Jiawei; Liu, Xihan; Lin, Cunhu; Wang, Jianping; Liu, Jun (Frontiers in Oncology, 2021)
Background: The relationship between tumor size and survival in intrahepatic cholangiocarcinoma (ICC) is still controversial. This study aimed to evaluate the prognostic ability of tumor size for solitary ICC after resection and explore optimal cut-off values in different subgroups. Methods: Patients with solitary ICC who underwent liver resection from the Surveillance, Epidemiology, and End Results Program and Shandong Provincial Hospital were retrospectively analyzed. Kaplan-Meier and Cox regression analysis were used to assess the prognostic ability of tumor size. The log-rank test was used to determine the optimal cut-off values, and a minimum P was regarded as the optimal one in different subgroups. Results: Large tumor size groups had worse overall survival (OS) than small tumor size groups. Cox regression analysis suggested that tumor size was an independent prognostic factor for OS for solitary ICC after resection. Subgroup analysis showed tumor size was associated with OS for both solitary ICC with and without vascular invasion (VI). Furthermore, the optimal cut-off values for solitary ICC with and without VI were found to be 8 cm and 3 cm, respectively, which could divide the patients into two groups with significant differences in OS. Conclusion: Tumor size was an independent prognostic factor for solitary ICC after resection. The existing American Joint Committee on Cancer (AJCC) staging system could be improved if the cut-off value of the T1 stage was changed to 8 cm and if the T2 stage incorporated a tumor size with a cut-off value of 3 cm. Further studies with more cases are needed to validate these findings.